Psychological predispositions and the inefficacy of the general anti-avoidance rules as determinants of tax evasion in South Africa - Nyaude, Ashley (University of Pretoria, 2023)
Mini Dissertation (LLM (Tax Law))--University of Pretoria, 2022.